Mortality, Recurrence, and Dependency Rates Are Higher after Acute Ischemic Stroke in Elderly Patients with Diabetes Compared to Younger Patients - Long, Xue; Lou, Yongzhong; Gu, Hongfei; Guo, Xiaofei; Wang, Tao; Zhu, Yanxia; Zhao, Wenjuan; Ning, Xianjia; Li, Bin; Wang, Jinghua; An, Zhongping (Frontiers in Aging Neuroscience, 2016)
Stroke has a greater effect on the elderly than on younger patients. However, the long-term outcomes associated with stroke among elderly patients with diabetes are unknown. We aimed to assess the differences in long-term outcomes between young and elderly stroke patients with diabetes. A total of 3,615 acute ischemic stroke patients with diabetes were recruited for this study between 2006 and 2014. Outcomes at 12 and 36 months after stroke (including mortality, recurrence, and dependency) were compared between younger (age <75 years) and elderly (age ≥75 years) patients. The elderly group included 692 patients (19.1%) overall. Elderly patients were more likely than younger patients to have a Trial of Org 10172 in Acute Stroke Treatment classification of stroke due to cardioembolism, moderate and severe stroke, and atrial fibrillation, but less likely to have hypertension and dyslipidemia, current smokers, and alcohol consumers. Mortality, dependency, and recurrence rates at 12 months after stroke were 19.0%, 48.5%, and 20.9% in the elderly group and 7.4%, 30.9%, and 15.4% in the younger group, respectively (all P < 0.05). Corresponding rates at 36 months after stroke were 35.4%, 78.7%, and 53.8% in the elderly group and 13.7%, 61.7%, and 43.0% in the younger group, respectively (all P < 0.001). The mortality, dependency, and recurrence rates at 12 and 36 months after stroke were significantly higher in the elderly group than in the younger group after adjusting for stroke subtypes, stroke severity, and risk factors. Odds ratios (95% confidence interval) at 12 and 36 months after stroke were 2.18 (1.64-2.89) and 3.10 (2.35-4.08), respectively, for mortality, all P < 0.001; 1.81 (1.49-2.20) and 2.04 (1.57-2.34), respectively, for dependency, all P < 0.001; and 1.37 (1.06-1.76) and 1.40 (1.07-1.85), respectively, for recurrence, P = 0.016. The findings from this study suggest that management and secondary prevention should be emphasized in elderly patients with diabetes in China to reduce mortality, recurrence, and dependency after stroke.